Triclocarban exposure exaggerates colitis and colon tumorigenesis: roles of gut microbiota involved. Issue 1 (9th November 2020) - Yang, Haixia; Sanidad, Katherine Z.; Wang, Weicang; Xie, Minhao; Gu, Min; Cao, Xiaoqiong; Xiao, Hang; Zhang, Guodong
ABSTRACT: Triclocarban (TCC) is a widely used antimicrobial ingredient in consumer products and is a ubiquitous contaminant in the environment. In 2016, the FDA removed TCC from over-the-counter handwashing products, but this compound is still approved for use in many other personal care products. A better understanding of its impact on human health could lead to significant impact for public health and regulatory policies. Here we show that exposure to low-dose TCC exaggerated the severity of colitis and exacerbated the development of colitis-associated colon tumorigenesis, via gut microbiota-dependent mechanisms. Exposure to TCC increased dextran sodium sulfate (DSS)- and interleukin 10 (IL-10) knockout-induced colitis, and exaggerated azoxymethane (AOM)/DSS-induced colon tumorigenesis in mice. Regarding the mechanisms, TCC exposure reduced the diversity and altered the composition of gut microbiota and failed to promote DSS-induced colitis in mice lacking the microbiota, supporting that the presence of the microbiota is critical for the pro-colitis effects of TCC. Together, these results support TCC could be a novel risk factor for colitis and colitis-associated colon cancer, and further regulatory policies on this compound could be needed.